A review on - fabrication and testing methods of aluminium metal matrix nano composites for various applications. (2022) - Theja, P. Charan; Suresh, R.; Reddy, M. Chandra Sekhara
Abstract: Nowadays the use of Aluminium-based Nanocomposites is increased in aerospace, automotive and marine industries. Aluminium Metal Matrix Nano Composites (AMMNCs) have an excellent combination of mechanical and physical properties such as stiffness, strength, hardness, lightweight and high thermal resistance as compared to the conventional materials. Nano reinforcements like SiC, Al2 O3, AlC, B4 C, CNT, Ni, Ti etc., can be mixed in aluminium in the form of particles or whiskers. The grain-reinforced composite material has better plastic forming ability than the whisker or fiber reinforced composite material. According to several works of literature, the mechanical properties of AMMNCs are greatly influenced by the parameters like reinforcement material, grain size and percentage of reinforcement. It is believed that the materials choice, microstructural highlights, assembling and handling boundaries, and so on affect the weariness reaction of MMNCs.